2019
DOI: 10.1038/s12276-019-0309-0
|View full text |Cite
|
Sign up to set email alerts
|

Deacetylation of XBP1s by sirtuin 6 confers resistance to ER stress-induced hepatic steatosis

Abstract: The active spliced form of X-box-binding protein 1 (XBP1s) is a key modulator of ER stress, but the functional role of its post-translational modification remains unclear. Here, we demonstrate that XBP1s is a deacetylation target of Sirt6 and that its deacetylation protects against ER stress-induced hepatic steatosis. Specifically, the abundance of acetylated XBP1s and concordant hepatic steatosis were increased in hepatocyte-specific Sirt6 knockout and obese mice but were decreased by genetic overexpression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…Consistent with this finding, SIRT6 and miR‐122 negatively regulate each other to coregulate the FA β‐oxidation 260 . Moreover, SIRT6 deacetylation may also exert liver protection by transcriptionally activating XBP1s, which confer resistance to ER stress‐induced hepatic steatosis 50 . In addition, SIRT6 activation may alleviate liver fibrosis by suppressing SMAD 2/3 signaling to affect hepatic stellate cells activation or transcriptionally inhibiting activity of orphan nuclear receptor estrogen‐related receptor γ (ERR‐γ) to impact bile acid production, representing a new therapeutic potential for treating nonalcoholic steatohepatitis (NASH) and cholestatic liver injury, respectively 52,53,261 .…”
Section: Human Diseasessupporting
confidence: 59%
See 1 more Smart Citation
“…Consistent with this finding, SIRT6 and miR‐122 negatively regulate each other to coregulate the FA β‐oxidation 260 . Moreover, SIRT6 deacetylation may also exert liver protection by transcriptionally activating XBP1s, which confer resistance to ER stress‐induced hepatic steatosis 50 . In addition, SIRT6 activation may alleviate liver fibrosis by suppressing SMAD 2/3 signaling to affect hepatic stellate cells activation or transcriptionally inhibiting activity of orphan nuclear receptor estrogen‐related receptor γ (ERR‐γ) to impact bile acid production, representing a new therapeutic potential for treating nonalcoholic steatohepatitis (NASH) and cholestatic liver injury, respectively 52,53,261 .…”
Section: Human Diseasessupporting
confidence: 59%
“…SIRT6 may also regulate the enzymatic activity of nicotinamide phosphoribosyltransferase (NAMPT) and the secretion of extracellular NAMPT (eNAMPT) by modifying the acetylation level on K53 and K369, respectively, which results in the regulation of intracellular nicotinamide adenine dinucleotide phosphate (NADPH) levels and conferring resistance to oxidative stress 49 . In addition, the spliced form of X‐box‐binding protein 1 (XBP1s) was deacetylated by SIRT6 at Lys257 and Lys297 residues to promote its degradation and consequently attenuate ER stress‐induced hepatic steatosis 50 . Moreover, SIRT6‐mediated activation of SOD2/Prdx6 pathway is pivotal for antidepressant response, which requires directing binding of SIRT6 to superoxide dismutase 2 (SOD2) and peroxiredoxin 6 (Prdx6), subsequently deacetylating them at Lys68/122 and Lys63/209, respectively 51 .…”
Section: Enzymatic Functionmentioning
confidence: 99%
“…Several studies showed that Sirt6 in hepatocytes protected against hepatic steatosis, insulin resistance, and inflammation. (17,(46)(47)(48) Because steatosis and inflammation are risk factors for HSC activation and liver fibrosis, it is possible that Sirt6 in hepatocytes may also participate in the initiation or progression of liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…5B,D). Hepatic steatosis is known to cause increased expression of spliced variant of Xbp-1 mRNA [33]. However, deletion of XBP-1 or IRE1α in the liver is also known to cause hepatic steatosis [11,34].…”
Section: Discussionmentioning
confidence: 99%